DLSU signed a letter of agreement with the Entrepreneurs Society of the Philippines - Business Management Department-De La Salle University, Manila (Animo Repository, 1993)
De La Salle University signed a letter of agreement with the Entrepreneurs Society of the Philippines which took effect in January, 1994. Present during the signing were Murine Distor, President of ESP, Renato Esguerra, Director General, ESP, Gloria Chavez, Chairperson of the Business Management Dept., and E. Formilleza, Dean, College of Business & Economics.